1994
DOI: 10.1093/ajh/7.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cardiovascular Responses to Exercise During the Development of Obesity in Dogs

Abstract: This study examined the control of cardiovascular dynamics in response to exercise during the development of obesity in dogs. Left atrial pressure (LAP), mean arterial pressure, and cardiac output (CO) were determined both at rest and in response to treadmill exercise (5.6 km/h, 10% grade) first during a control, lean state and then, once a week while the dogs were maintained on a high fat diet (HFD) for 4 weeks. Body weight increased from 22.8 +/- 1.1 to 33.1 +/- 2.0 kg after 4 weeks of HFD. The dogs develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…43,44 The animal model of obesity also exhibits many of the features of human obesity, including various metabolic disturbances as well as the HT and resting HR that occur in parallel with weight gain. 45,46 Those adolescents with obesity, tachycardia, and HT may be on the way to having a full set of risk factors for metabolic syndrome and may be at a high risk of subsequent atherosclerotic diseases early in adult life. Therefore, the prevention and reduction of these risk factors by changing lifestyle, especially by promoting exercise and favorable eating behaviors, is fundamental to the prevention of atherosclerotic diseases later in life.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The animal model of obesity also exhibits many of the features of human obesity, including various metabolic disturbances as well as the HT and resting HR that occur in parallel with weight gain. 45,46 Those adolescents with obesity, tachycardia, and HT may be on the way to having a full set of risk factors for metabolic syndrome and may be at a high risk of subsequent atherosclerotic diseases early in adult life. Therefore, the prevention and reduction of these risk factors by changing lifestyle, especially by promoting exercise and favorable eating behaviors, is fundamental to the prevention of atherosclerotic diseases later in life.…”
Section: Discussionmentioning
confidence: 99%
“…73 A limitation of all these studies is that blood pressure was measured by tail cuff, a method that yields much more variable results than state of the art techniques by telemetry. 74 Furthermore, rats may not be the best model to study obesity-induced hypertension as, even within the same strain of rats (Sprague-Dawley), feeding rats a high-fat diet does not always produce hypertension, 75 whereas dogs 76,77 and rabbits 78 show consistent increase in blood pressure with diet-induced obesity. The association of weight cycling and hypertension has been investigated in many human studies, often with positive results.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…13 In dogs, we have demonstrated that weight-gain with a high-fat diet for 4 weeks led to a significant increase in left atrial pressure, both at rest and more importantly during exercise, and to a net decrease in exercise tolerance. 12 In addition, obese rabbit hearts exhibit mild systolic dysfunction with a reduced contractile responsiveness to isoproterenol. 14 To what extent the cardiac changes observed in obesity are due to ectopic fat storage is not clear.…”
Section: Ectopic Fat Storage In the Heartmentioning
confidence: 99%
“…6,7 Similar findings are observed when dogs are fed a high-fat diet for several weeks. 11,12 A model of obesity based solely on intake of a high-fat diet is relevant to the development of obesity in many situations in humans. As obese dogs and rabbits exhibit many of the characteristics of obesity in humans, including hypertension, insulin resistance, humoral activation, increase in lean body mass and cardiac hypertrophy, they serve as a good model to study the cardiovascular effects of ectopic fat storage.…”
Section: Introductionmentioning
confidence: 99%